2017
DOI: 10.1103/physrevb.96.224401
|View full text |Cite
|
Sign up to set email alerts
|

Noncollinear magnetic ordering in the Shastry-Sutherland Kondo lattice model: Insulating regime and the role of Dzyaloshinskii-Moriya interaction

Abstract: We investigate the necessary conditions for the emergence of complex, noncoplanar magnetic configurations in a Kondo lattice model with classical local moments on the geometrically frustrated Shastry-Sutherland lattice and their evolution in an external magnetic field. We demonstrate that topologically nontrivial spin textures, including a new canted flux state, with nonzero scalar chirality arise dynamically from realistic short-range interactions. Our results establish that a finite Dzyaloshinskii-Moriya (DM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Further, the use of an external Zeeman field enhances the possibility of having noncoplanar phases significantly. Previously, we have shown that the Kondo lattice model on the SS lattice exhibits noncoplanar and noncollinear ground states over a wide range of parameters [46][47][48]. In this work, we aim to thoroughly study the effect of all the competing interactions in stabilizing the noncoplanar phases and investigate the transport properties of itinerant electrons on this lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the use of an external Zeeman field enhances the possibility of having noncoplanar phases significantly. Previously, we have shown that the Kondo lattice model on the SS lattice exhibits noncoplanar and noncollinear ground states over a wide range of parameters [46][47][48]. In this work, we aim to thoroughly study the effect of all the competing interactions in stabilizing the noncoplanar phases and investigate the transport properties of itinerant electrons on this lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Here we present the results of our investigation of topological magnons in the recently proposed flux state, that is stabilised by DMI perpendicular to the lattice plane in the SS lattice [58].In presence of in plane DMI, this evolves to the canted flux state -the resulting magnon bands in an external longitudinal magnetic field, carry non-zero Chern numbers that determine the topological character of the magnon bands. Varying the different components of the DMI result in a sequence of band topological transitions where the Chern number for the magnon bands change over a wide range of possible values.…”
Section: Introduction 81mentioning
confidence: 87%
“…The rare-earth tetraborides are the material realization for frustrated SS-lattices because the antiferromagnetic Heisenberg-interactions on the dimer and axial bonds are nearly equal (J ≈ J ) [55,56,57]. Shahzad et al [58] show that for a classical spin systems in RB 4 , crystal-symmetry allowed perpendicular DMI on the axial bond gives rise to coplanar flux state (see Fig. 1.1(b)).…”
Section: Background and Motivationsmentioning
confidence: 99%
See 2 more Smart Citations